High resolution computed tomography and chest x-ray findings in patient with pulmonary tuberculosis - Pant, Chiranjibi; Pal, Anusmriti; Yadav, Manoj Kumar; Shrestha, Bishow Kumar (Journal of Chitwan Medical College, 2019)
Background: Pulmonary Tuberculosis (PTB) is a major public health problem in Nepal. Diagnosis of pulmonary tuberculosis is done by bacteriological confirmation of respiratory specimen however Negative smear needs clinical and radiological evaluation for the diagnosis in suspected patient. This study focuses on radiological findings in both Pulmonary bacteriologically confirmed (PBC) and pulmonary clinically diagnosed (PCD) Tuberculosis. Methods: This observational study was conducted at Chitwan Medical College between Feb 2019 to July 2019. 45 Patient diagnosed with PTB were enrolled. Chest X-ray (CXR) and High Resolution Computed Tomography (HRCT) chest reports were analysed for the presence of findings that suggest active infection like cavity, consolidation, tree in bud, etc in PBC and PCD. Results: A total of 45 PTB patients with mean age: 54.60 ± 19 years were included. 53.3 % were PBC and 46.7 % were PCD tuberculosis, CXR findings in PBC and PCD tuberculosis was nodular infiltrate 45.8% versus 2.4%, consolidation 45% versus 42.9%, cavity 8.3% versus 14.3% respectively however 12.5% PBC tuberculosis patient had a normal chest x-ray. HRCT chest in PBC and PCD showed cavity in 45.8% versus 23%, tree in bud 25% versus 52.4%, consolidation 62.5 versus 57.1%, ground glass opacity 29.2% versus 23.8% respectively and none of the HRCT chest was normal. In comparison to the CXR, HRCT chest shows more cavitary lesions in PBC and tree in bud was more common in PCD. Conclusions: This study has found that radiological findings suggestive of active PTB was more obvious in HRCT than CXR. Presence of cavity, lobar consolidation and tree in bud lesion in HRCT chest were more frequently observed in both PBC and PCD Tuberculosis.